2019
DOI: 10.7759/cureus.5797
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Ashwagandha (Withania somnifera) Root Extract in Insomnia and Anxiety: A Double-blind, Randomized, Placebo-controlled Study

Abstract: Introduction Insomnia is a prevalent sleep disorder that can profoundly impact a person's physical health and mental wellbeing. Most of the currently available drugs for insomnia exert adverse effects. Hence, alternative herbal therapies could be effective in treating insomnia. Ashwagandha, a proven "Rasayana" from ancient Ayurveda is having the required potential to treat insomnia. Objective To determine the efficacy and safety of Ashwagandha root extract in patients with insomnia and anxiety. Methods This wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(79 citation statements)
references
References 28 publications
(34 reference statements)
1
64
0
4
Order By: Relevance
“…A root extract that warrants special attention is Withania somnifera (most known as ashwagandha) given some research have found ergogenic effects in athletic [ 121 , 122 ] and physically active individuals [ 123 ]. Moreover, the adaptogenic, anti-inflammatory, and antioxidant properties of ashwagandha [ 124 , 125 , 126 ] turns this herbal extract into a potential strategy to optimize recovery and promote exercise-induced adaptations. Although more research is required, dosages are between 300 and 500 mg of aqueous root extract twice per day.…”
Section: Resultsmentioning
confidence: 99%
“…A root extract that warrants special attention is Withania somnifera (most known as ashwagandha) given some research have found ergogenic effects in athletic [ 121 , 122 ] and physically active individuals [ 123 ]. Moreover, the adaptogenic, anti-inflammatory, and antioxidant properties of ashwagandha [ 124 , 125 , 126 ] turns this herbal extract into a potential strategy to optimize recovery and promote exercise-induced adaptations. Although more research is required, dosages are between 300 and 500 mg of aqueous root extract twice per day.…”
Section: Resultsmentioning
confidence: 99%
“…Scientific reports suggested that Ashwagandha contains sleep-inducing compounds that aid in better sleep in all age groups. We reported a similar impact of Ashwagandha root extract on insomnia and anxiety recently [28]. Equivalent to modern geriatric medicine, "Jara Chikitsa" (Aging treatment) and "Jara Vyadhi" (Agingassociated diseases), remained an important part of the classical Ayurvedic treatment process where Ashwagandha is recommended as one of the most effective solutions [29].…”
Section: Discussionmentioning
confidence: 96%
“…For some ingredients of the studied dietary supplement, there is little/moderate evidence of a clinical effect in patients with sleeping disorders: the essential amino acid L-tryptophan, which is a precursor of the endogenous melatonin and serotonin synthesis, is often used to treat insomnia and depression, 17 , 18 and sparse evidence suggests that ashwagandha extract can improve insomnia and anxiety. 19 , 20 However, there are no comparative studies reported in the literature, and general transferability of study results is hardly feasible because ingredients and composition of the studied dietary supplements differ.…”
Section: Discussionmentioning
confidence: 99%